MODEL PEMBELAJARAN PEER-TEACHING UNTUK MENINGKATKAN KEMAMPUAN VERBAL MAHASISWA PGSD FKIP UMS - Rubino - Rubiyanto (Profesi Pendidikan Dasar, 2014)
The problems of lecturing in Primary Education are lowering the ability of verbal communication.The student seldom gives good respond in the form of question, expostulationand or criticism. For the developed of verbal capacity, researcher applied the strategyof peer-teaching. Peer-Teaching is a lecturing model by functioned the student arelearning friend each other. There are six models, one of them is Jigsaw learning. Theimplementation of Jigsaw model is by counting six times, and each is observed by assistant.The general conclusion of the research is that it can improve the student’s verbalcapacity until significant number (92,5 %). In detail it can be elaborated: a) The enthusiasmof the student in working task, getting better by the end of meeting counted 42students. b) The student activity of instruction of the material rounding into 43 students, c) The student of enough question and answer capacity rounding into the goodness are37 student, d) The interaction of student of good verbal remain to be good are 43 students.From final test also told that the final achievement of the students amount B.